2013
DOI: 10.11646/zootaxa.3741.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Using various lines of evidence to identify Chironomus species (Diptera: Chironomidae) in eastern Canadian lakes

Abstract: Chironomus Meigen (Diptera, Chironomidae) larvae are usually the largest sediment-burrowing chironomids, and as such often constitute a major part of the freshwater infaunal biomass. However, use of this genus in ecological, environmental and paleoecological studies is hampered by the fact that Chironomus larvae are difficult to identify to species because the larvae of many species are morphologically similar. We used a combination of morphological, cytological and genetic techniques to distinguish Chironomus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…The interspecific genetic divergence observed in our data is in accordance with results for other groups of Chironomidae and other aquatic Diptera families, with values around 15% (Beckenbach and Borkent 2003; Sinclair and Gresens 2008; Proulx et al 2013; Silva et al 2013), corroborating the hypothesis that Groups A and B represents at least two distinct species. Group A is composed of specimens identified as Chironomus striatipennis and Chironomus kiiensis from different regions of Asia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The interspecific genetic divergence observed in our data is in accordance with results for other groups of Chironomidae and other aquatic Diptera families, with values around 15% (Beckenbach and Borkent 2003; Sinclair and Gresens 2008; Proulx et al 2013; Silva et al 2013), corroborating the hypothesis that Groups A and B represents at least two distinct species. Group A is composed of specimens identified as Chironomus striatipennis and Chironomus kiiensis from different regions of Asia.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the genetic intraspecific divergence in some Chironomidae genera have reported values between 0.5 and 2.3% (Sinclair and Gresens 2008; Silva et al 2013; Proulx et al 2013; Trivinho-Strixino et al 2012). Similar values were observed in studies on other insects, including some Diptera families (e.g., Beckenbach and Borkent 2003; Hamada et al 2010; Hernández-Triana et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In OTU 13, a reference sequence and a sequenced adult were classified as different species within the genus Chironomus. For some Chironomus species, the COI barcode and morphological identification alone may be inadequate for establishing species level identifications (Ekrem et al, 2010, Proulx et al, 2013 For example, C. quinnitukqut is a part of the C. decorus group, and species within this group are often separated based on karyotype analysis (Martin et al, 2011). In OTU 21, Dicrotendipes simpsoni represents a species within the Dicrotendipes lucifer complex.…”
Section: Ambiguities Inconsistencies and Possible Errorsmentioning
confidence: 99%
“…
Currently there are nine larval types in the genus Chironomus based on the presence, absence or structure of the lateral and ventral tubules (Proulx et al 2013). We are now proposing a tenth type based on the posterior prolegs and the arrangement of the anal tubules -the yama-type.The reason for adding this type and the basis of the name is as follows:In 1980, Sublette and Martin described a new genus Yama, closely related to Chironomus, An unusual feature of the larva of Yama, not specifically mentioned in the description but illustrated in their figure 5a is the relatively long, rather tanypodine-like posterior prolegs, along with a 'star' arrangement of the anal tubules.Recently, one of us (DSC) collected very similar larvae from Manipur, India.
…”
mentioning
confidence: 99%
“…Currently there are nine larval types in the genus Chironomus based on the presence, absence or structure of the lateral and ventral tubules (Proulx et al 2013). We are now proposing a tenth type based on the posterior prolegs and the arrangement of the anal tubules -the yama-type.…”
mentioning
confidence: 99%